PERTANGGUNGJAWABAN ORANGTUA KANDUNG DALAM KASUS KECELAKAAN LALU LINTAS YANG DIALAMI OLEH ANAK SEBAGAI TERSANGKA DI WILAYAH HUKUM POLRES SLEMAN - Rachmad Wijayanto; Francisca Romana Harjiyatni; Hartanti Hartanti (Kajian Hasil Penelitian Hukum, 2018)
This study aims to analyze the implementation of criminal liability by parents as a result of traffic accidents experienced by children in the area of Polres Sleman and criminal alternative in order to be legal protection for children and fulfillment of human rights of children, because in principle the accident that befell children general there is certainly a parent's share is not wise in making decisions.The approach used by the author is the normative juridical approach. Normative research is a legal research conducted by examining library materials or secondary. The research conducted by the writer is to analyze how the criminal responsibility done by the parent as a result of the traffic accidents case experienced by the child in Sleman Police area and criminal alternative in order to be able to legal protection for children and the fulfillment of the human rights of the child.The criminal liability of the parent in case of traffic accidents experienced by the Child in the Sleman Police territory in the application can not be done, because based on the elements of criminal offense in the liability process must be done by the person doing the act intentionally or negligence, positively applicable in Indonesia under Article 77 of the Indonesian Criminal Code states that "The authority to prosecute the crime shall be abolished if the defendant dies." Based on this matter it shows that a criminal act will disappear by itself when the person committing the crime has died, meaning that criminal liability is a part of personal responsibility, other than that alternative criminal responsibility if parents can not do it, then based on the existing positive law alternative criminal responsibility is not implemented, this is because the offender in this case has died, because it has been denied his criminal responsibility cannot be imposed, because the proceedings of the case under Article 77 of the Criminal Code of prosecution are deleted by law. The problem that arises is the existence of compensation or compensation so this process is not from the accountability process criminal, but more moral reason as human beings to be responsible.                                Keywords: Criminal Accountability, Parents, Traffic Accidents